Clinical Supervision as One of The Elements of Developing Educational Resources - Ihwan Mahmudi; Nur Reformawati; Ulfiatul Hasanah (Departement of Mathematics Education, 2023)
Education is an effort designed to achieve the goals that have been set to improve the quality of human resources. One of these efforts is to go through a learning process. In an effort to improve the quality of educational resources, teachers are a component of human resources that must be fostered and developed continuously. The establishment of the teacher profession is carried out through pre-service education programs and in-service programs. Not all teachers who educate in educational institutions are well trained and qualified. The potential of teacher resources needs to continue to grow and develop in order to perform their functions potentially. In addition, the influence of fast-paced changes encourages teachers to continuously learn to adjust to the development of science and technology and community mobility. Supervision is training given to all school staff so that they are able to improve their ability to develop a better teaching and learning situation. The purpose of educational supervision is to develop a situation of seeking better teaching knowledge through training and improving teaching. One of the factors that affect the quality of education of a school is student learning achievement, where the learning achievement is influenced by the performance and quality of the teacher. Therefore, the principal and supervisor as supervisors must be able to improve, maintain the performance and quality of teacher professionalism. One of the efforts that can be done is to supervise the teacher's performance continuously.